Dual-Specificity Phosphatase 4 Overexpression in Cells Prevents Hypoxia/Reoxygenation-Induced Apoptosis via the Upregulation of eNOS - Dougherty, Julie A.; Kilbane Myers, Joanna; Khan, Mahmood; Angelos, Mark G.; Chen, Chun-An (Frontiers in Cardiovascular Medicine, 2017)
MAPK signaling cascades regulate several cellular functions, including differentiation, proliferation, survival and apoptosis. The duration and magnitude of phosphorylation of these MAPKs are decisive determinants of their physiological functions. DUSPs exert kinetic control over these signaling cascades. Previously, we demonstrated that DUSP4-/- hearts sustain a larger infarct and have poor functional recovery, when isolated hearts were subjected to ischemia/reperfusion (I/R). Uncontrolled p38 activation and up-regulation of Nox4 expression are the main effectors for this functional alteration. Here, DUSP4 over-expression in endothelial cells was used to investigate the role of DUSP4 on the modulation of ROS generation and vascular function, when cells were subjected to hypoxia/re-oxygenation (H/R) insult. Immunostaining with cleaved caspase-3 revealed that DUSP4 over-expression prevents caspase-3 activation and apoptosis after H/R. The beneficial effects occur via modulating p38 activity, increased NO bioavailability, and reduced oxidative stress. More importantly, DUSP4 over-expression up-regulates eNOS protein expression (1.62  0.33 versus 0.65  0.16) during H/R-induced stress. NO is a critical small molecule involved in regulating vascular tone, vascular growth, platelet aggregation, and modulation of inflammation. The level of NO generation determined using DAF-2 fluorescence demonstrated that DUSP4 over-expression augments NO production, and thus improves vascular function. The level of superoxide generated from cells after being subjected to H/R was determined using DHE-HPLC method. The results suggested that DUSP4 over-expression in cells decreases H/R-induced superoxide generation (1.56 ± 0.14 versus 1.19 ± 0.05) and thus reduces oxidant stress. This also correlates to the reduction in the total protein S-glutathionylation, an indicator of protein oxidation. These results further support our hypothesis that DUSP4 is an antioxidant gene and a key phosphatase in modulating MAPKs, especially p38, during oxidative stress; which regulates ROS generation and eNOS expression and thus protects against oxidant-induced injury or apoptosis. Overall, DUSP4 may serve as an excellent molecular target for the treatment of ischemic heart disease.